The impact of idealism, Volume 3, Aesthetics and literature the legacy of Post-Kantian German thought - Jamme, Christoph; Cooper, Ian 1979-; Boyle, Nicholas; Disley, Liz (Cambridge University Press, 2013)
The first study of its kind, The Impact of Idealism assesses the impact of classical German philosophy on science, religion and culture. This third volume explores German Idealism's impact on the literature, art and aesthetics of the last two centuries. Each essay focuses on the legacy of an idea or concept from the high point of German philosophy around 1800, tracing out its influence on the intervening period and its importance for contemporary discussions. As well as a broad geographical and historical range, including Greek tragedy, George Eliot, Thomas Mann and Samuel Beckett, and key musicians and artists such as Wagner, Andy Warhol and Frank Lloyd Wright, the volume's thematic focus is broad. Engaging closely with the key aesthetic texts of German Idealism, this collection uses examples from literature, music, art, architecture and museum studies to demonstrate Idealism's continuing influence
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Idealism, German